System identification and H∞-based control of quadrotor attitude. (1st January 2020) - Noormohammadi-Asl, Ali; Esrafilian, Omid; Ahangar Arzati, Mojtaba; Taghirad, Hamid D.
Highlights: A black-box continuous-time system identification based on the experimental data. Setting proper uncertainty, input, and sensitivity weighting functions. Synthesizing the H ∞ controller based on the obtained linear model. Implementing of H ∞ controller on the real robot and evaluating its performance. Comparing with PID and μ synthesis controllers in the presence of disturbance and wind. Abstract: The attitude control of a quadrotor is a fundamental problem, which has a pivotal role in a quadrotor stabilization and control. What makes this problem more challenging is the presence of uncertainty such as unmodelled dynamics and unknown parameters. In this paper, to cope with uncertainty, an H ∞ control approach is adopted for a real quadrotor. To achieve H ∞ controller, first a continuous-time system identification is performed on the experimental data to encapsulate a nominal model of the system as well as a multiplicative uncertainty. By this means, H ∞ controllers for both roll and pitch angle are synthesized. To verify the effectiveness of the proposed controllers, some real experiments and simulations are carried out. Results verify that the designed controller does retain robust stability, and provide a better tracking performance in comparison with a well-tuned PID and a μ synthesis controller.